PERSONIFIKASI DALAM LIRIK LAGU ALBUM ORANGE GARDEN POP KARYA YOSHIOKA YUI - I Wayan Ferdy Chandra Palguna; Ni Wayan Meidariani; Betty Aritonang (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2022)
This research aims to analyze and describe the use of personification style in the song lyrics of the Orange Garden Pop, an album by Yoshioka Yui. This research used stylistic theory and the definition of style by Gorys Keraf. The data collection method and technique used in this research are the method of listening and the note-taking technique. Descriptive qualitative method for the data analysis method. Then, the method for presenting the results of the data analysis used informal method. The results based on this research showed that from the song lyrics there are 7 personification styles used to disguise the original meaning of the song lyrics entitled Feel My Soul, Merry Go Round, Rain, Oh Yeah and Love & Truth so as to have an effect that can play with the listener's feelings which are able to give feelings of pleasant, touching, sadness, and thrilling.